A forward view for Digital Discovery: the scientific challenges of the twenty-first century require accelerated discovery approaches. (3rd February 2022) - Aspuru-Guzik, Alán
Abstract : In his inaugural Editorial, the Editor-in-Chief of Digital Discovery introduces the new, emerging field of 'accelerated science' and explains what his expectations are of the articles to be included in this new exciting journal.